Functionalized Surface Geometries Induce: “Bone: Formation by Autoinduction” - Ripamonti, Ugo (Frontiers in Physiology, 2018)
The induction of tissue formation, and the allied disciplines of tissue engineering and regenerative medicine, have flooded the twenty-first century tissue biology scenario and morphed into high expectations of a fulfilling regenerative dream of molecularly generated tissues and organs in assembling human tissue factories. The grand conceptualization of deploying soluble molecular signals, first defined by Turing as forms generating substances, or morphogens, stemmed from classic last century studies that hypothesized the presence of morphogens in several mineralized and non-mineralized mammalian matrices. The realization of morphogens within mammalian matrices devised dissociative extractions and chromatographic procedures to isolate, purify, and finally reconstitute the cloned morphogens, found to be members of the transforming growth factor-β (TGF-β) supergene family, with insoluble signals or substrata to induce de novo tissue induction and morphogenesis. Can we however construct macroporous bioreactors per se capable of inducing bone formation even without the exogenous applications of the osteogenic soluble molecular signals of the TGF-β supergene family? This review describes original research on coral-derived calcium phosphate-based macroporous constructs showing that the formation of bone is independent of the exogenous application of the osteogenic soluble signals of the TGF-β supergene family. Such signals are the molecular bases of the induction of bone formation. The aim of this review is to primarily describe today's hottest topic of biomaterials' science, i.e., to construct and define osteogenetic biomaterials' surfaces that per se, in its own right, do initiate the induction of bone formation. Biomaterials are often used to reconstruct osseous defects particularly in the craniofacial skeleton. Edentulism did spring titanium implants as tooth replacement strategies. No were else that titanium surfaces require functionalized geometric nanotopographic cues to set into motion osteogenesis independently of the exogenous application of the osteogenic soluble molecular signals. Inductive morphogenetic surfaces are the way ahead of biomaterials' science: the connubium of stem cells on primed functionalized surfaces precisely regulates gene expression and the induction of the osteogenic phenotype.